2019
DOI: 10.3389/fnbot.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Control Mechanism for Determination of Moving Direction in Brittle Stars With Penta-Radially Symmetric Body

Abstract: A brittle star, an echinoderm with penta-radially symmetric body, can make decisions about its moving direction and move adapting to various circumstances despite lacking a central nervous system and instead possessing a rather simple distributed nervous system. In this study, we aimed to elucidate the essential control mechanism underlying the determination of moving direction in brittle stars. Based on behavioral findings on brittle stars whose nervous systems were lesioned in various ways, we propose a phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Astley [12] described their turning behaviour in a short-term series, which was performed by changing the roles of arms rather than by rotating their body axis. Regarding escape situations, studies have reported that brittle stars avoid open or bright spaces [19,33], predator extracts [32] and KCl solution [10,11]. However, few studies have focused on how each arm reacts to such repellents and defines the direction of the movement of an individual.…”
Section: Deciding Moving Directionmentioning
confidence: 99%
See 4 more Smart Citations
“…Astley [12] described their turning behaviour in a short-term series, which was performed by changing the roles of arms rather than by rotating their body axis. Regarding escape situations, studies have reported that brittle stars avoid open or bright spaces [19,33], predator extracts [32] and KCl solution [10,11]. However, few studies have focused on how each arm reacts to such repellents and defines the direction of the movement of an individual.…”
Section: Deciding Moving Directionmentioning
confidence: 99%
“…Kano et al [11] proposed a model in which arm movements become potentially symmetrical to aversive stimulation. We initially expected such a symmetrical scheme to allow the animal to escape opposite to the stimulus.…”
Section: Deciding Moving Directionmentioning
confidence: 99%
See 3 more Smart Citations